A novel patient friendly IT enabled framework for selection of desired healthcare provider. (2019) - Silas, Salaja; Rajsingh, Elijah Blessing
The healthcare providers have tremendously grown during the past decade. Selecting a healthcare provider based on patient's preference is really a great challenge. The purpose of this paper is to provide an IT enabled framework that will help the patients to find a suitable healthcare provider based on their preferences. The patients' preferences in selecting a healthcare provider differ based on their geographical region, gender, age and socio-economic background. Discovering a set of feasible healthcare providers and selecting the most appropriate healthcare provider based on the patient preferences can be modelled as a multi-criteria decision making problem. In this article, a novel patient friendly framework is proposed for selecting the best healthcare provider. Even with a huge dataset, the results show that the proposed framework is robust, reliable, faster and effective. The analysis reveals that the number of preferences and the healthcare providers influence the healthcare selection time. Case studies on 500 patients from different geographical regions reveal that the proposed framework is effective.